2021
DOI: 10.31272/jeasd.25.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Impact Load on the Performance of Concrete Slabs Reinforced by CFRP Bars

Abstract: Using FRP bars in the concrete structures under harsh environment produces extension of those service life and dropping of the cost of their lifecycle. This study investigated the influence of slab thickness, material of rebar, arrangement of reinforcement and mass’s dropped on the dynamic behavior of RC slabs by using laboratory experiments. Seven specimens 1550×1550 mm dimension with two thickness 120 and 150mm, single control specimen reinforced with steel bars and six specimens reinforced by CFRP bars were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
(6 reference statements)
2
2
0
Order By: Relevance
“…There was a gradual decrease as the damage progressed because the concrete fragments were crushed to varying degrees before repair. This is similar to what was obtained from previous researchers Atefatdoost et al (2022) [21], Abed and Medhlom (2023) [22] and Shabestani et al (2022) [43]. They found that the most optimal array of the retrofitting material increases the capacities for two-way slabs by 18-30%.…”
Section: Load Capacitysupporting
confidence: 91%
See 2 more Smart Citations
“…There was a gradual decrease as the damage progressed because the concrete fragments were crushed to varying degrees before repair. This is similar to what was obtained from previous researchers Atefatdoost et al (2022) [21], Abed and Medhlom (2023) [22] and Shabestani et al (2022) [43]. They found that the most optimal array of the retrofitting material increases the capacities for two-way slabs by 18-30%.…”
Section: Load Capacitysupporting
confidence: 91%
“…Researchers Golham and Al-Ahmed (2024) [20] say that adding CFRP strips to concrete slabs with holes makes them more robust and able to handle more weight. It was found that CFRP laminates changed the strength and breakdown mode of the slabs, which is similar to what Abed and Medhlom found in 2023 [21]. All of our results together show that CFRP sheets might make thin concrete slabs much more potent when they are pulled apart.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results revealed that the plates reinforced with 75mm GFRP strips were more effective in mitigating the damage volume ratio compared to 50mm GFRP strips. [13] investigated the dynamic behavior of reinforced concrete slabs, slab thickness, rebar material, and reinforcement arrangement, and the effect of falling mass.…”
Section: Introductionmentioning
confidence: 99%